2007
DOI: 10.1002/pat.862
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel polyimides with 1‐octadecyl side chains for liquid crystal alignment layers

Abstract: A series of poly(amic acid)s have been synthesized from cyclobutane‐1,2,3,4‐tetracarboxylic dianhydride (CBDA), a functional diamine, 1‐(3,5‐diaminophenyl)‐3‐(1‐octadecyl)‐succinicimide and 4,4‐diaminodiphenylmethane (DDM) to give liquid crystal alignment layers with high pretilt angle after a rubbing process for vertically aligned liquid crystal display devices. Inherent viscosities of the poly(amic acid)s measured were in the range 0.2–1.56 dl/g, which decreased with an increase of content of 1‐(3,5‐diaminop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…It has been known that the high pretilt angles of LC molecules required to produce homeotropic alignment are related to the low surface energy values of the alignment layer and/ or the steric repulsions between the LC molecules and the alignment layers. 36,[49][50][51][52][53][54][55][56] Therefore, polyimides having long alkyl side groups have been widely used to align LCs perpendicular to the surface of the alignment layer, because the long alkyl groups can produce low surface energy layers due to their steric effect. 51,56 We also found that the LC alignment behavior on the polystyrene derivatives in this study could be ascribed to the surface energy values.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that the high pretilt angles of LC molecules required to produce homeotropic alignment are related to the low surface energy values of the alignment layer and/ or the steric repulsions between the LC molecules and the alignment layers. 36,[49][50][51][52][53][54][55][56] Therefore, polyimides having long alkyl side groups have been widely used to align LCs perpendicular to the surface of the alignment layer, because the long alkyl groups can produce low surface energy layers due to their steric effect. 51,56 We also found that the LC alignment behavior on the polystyrene derivatives in this study could be ascribed to the surface energy values.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the property of aligning, PI films need to induce LCM to certain pretilt angles for different display modes. For supertwisted nematic (STN) LCD, pretilt angles ranging from 5 to 20 are needed, particularly for vertical aligned nematic (VAN) LCD, where pretilt angles of 90 are a must (2). In order to raise the pretilt angles, side chains, mostly long and bulky, are incorporated into the PIs, which results in low molecular weight, and thus bad mechanical strength, of the resultant films.…”
Section: Introductionmentioning
confidence: 98%
“…The pretilt angle is correlated with some parameters of a supertwisted nematic (STN) mode LCD, and a high value is preferable for a good performance [1,2]. However, different display modes need different pretilt angles, for example, STN mode (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) [3], in-place switch mode (0 ) [4], and multidomain vertical alignment mode (90 ). Therefore, controlling the pretilt angle has become a topic of considerable interest in recent decades.…”
Section: Introductionmentioning
confidence: 99%